DC/DC converter in the electric vehicle traction system - Ivanov M. D.; Khazieva R. T. (Vestnik MGTU, 2023)
DC-DC converters are used in various electrical devices including the traction system of electric vehicles. Electric vehicles use synchronous motors with permanent magnets as drives. Their distinctive feature is the nonlinear dependence of the electromagnetic torque of the motor on its input voltage. One of the ways to improve the energy characteristics of an electric vehicle is to include a DC-DC converter in the engine power supply circuit. The study has examined the main types of DC-DC converters, studied their advantages and disadvantages; a method has been determined to increase the energy efficiency of an electric vehicle by using a multi-channel DC-DC converter as part of its power circuit. This structure makes it possible to reduce the requirements for individual power switches and converter elements, and is also optimal from the point of view of weight and size indicators, since converters of this type do not have a transformer. Based on the review, a multichannel DC-DC converter circuit has been selected for integration into the traction electric drive system. The Tesla Model S has been chosen as the base vehicle. Based on the calculated dynamic characteristics of the electric vehicle, main parameters of the DC-DC converter have been determined, computer simulation of the power plant of an electric vehicle with a DC-DC converter has been carried out in the Matlab Simulink software environment. The use of the converter improves the energy efficiency of vehicles, and is also a better solution compared to installing a battery with a higher voltage.